Occupational Diseases Workers’ Protection as a Important Aspect on OSH Program - Sudi Astono; Ma'ruf Akbar; Moch. Asmawi (Program Studi S3 Ilmu Manajemen, 2019)
Abstract The Aim of this study are to answer the question: